Empowerment of People with Disabilities through the Establishment of Joint Ventures and Entrepreneurship Training in Banjar City - Riza Faizal; Hasan Fahmi Kusnandar; Maman Sulaeman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The issue of disabilities is an always hot topic to be discussed not only in developing countries but also in developed countries. This is because groups with disabilities are a minority group whose fulfillment of their rights by the State often go unnoticed. Various efforts have been made by the central and local governments so that every element of society can be empowered in accordance with existing rules, but those efforts do not run smoothly, so that every program that aims to empower the community, as if it becomes a program that is normatively able to be treated with minimal. The purpose of this research is to analyze the empowerment of people with disabilities through the establishment of joint ventures and entrepreneurship training in Banjar City. The research method used is causality by analyzing the relationship between the phenomena examined. The population of this study is disability in Banjar City of 139 people and the determination of samples is carried out in a census. The results showed that the formation of joint ventures and entrepreneurial training can empower people with disabilities, in this case people with disabilities have business and income.